CT Number Conformity Test on Multislice CT Scan at Yogyakarta PDHI Islamic Hospital: Uji Kesesuaian CT Number pada CT Scan Multislice di Rumah Sakit Islam Yogyakarta PDHI - Mas'uul, Ali; Indrawati, Silviana; Handayani, Nita (Sunan Kalijaga Journal of Physics, 2024)
This research focuses on determining the CT number, which is the attenuation coefficient value of x-rays after passing through an organ. The level of energy attenuation depends on the initial energy of the x-rays and the atomic number of the object, which play a role in describing differences in the characteristics of organs or body tissues. This research aims to ensure the suitability of the CT number to obtain accurate information about CT scan images. Research procedures include observation, data collection, and data processing. The CT number data from the experimental results was then compared with the simulation results using IndoQCT software. The CT Number conformity test is carried out on a water phantom by adjusting the tube voltage, input current, and slice thickness. The Region of Interest (ROI) is made in the form of a circle at five measurement points, namely the central direction, 3 o'clock, 6 o'clock, 9 o'clock, and 12 o'clock. The research results, both direct testing and simulation using IndoQCT software, show that the CT number does not exceed the accuracy tolerance limit and uniformity, respectively, -4 ˂ HU ˂ +4 and -2 ˂ HU ˂ +2. Based on the analysis results, it can be concluded that the CT number measurements in the Radiology Unit at the Yogyakarta PDHI Islamic Hospital meet the requirements of BAPETEN Perka Number 2 of 2018.